Media Komunikasi Pemasaran Digital Marketing Produk Umkm Selama Pandemi Covid-19 - Mujayana, Marya; Santoso, Rudi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
This research focuses on the efforts of MSMEs to utilize digital means for marketing activities or processes. MSMEs use this digital facility for marketing communications to increase purchase intensity during the COVID-19 pandemic. This study uses a qualitative descriptive method with a literature review approach. This study aims to describe the condition of the object of research objectively based on visible facts and data. The thing of this research is 100 MSME entrepreneurs in Madiun Regency. The study results show that the communication strategies carried out by MSME actors in dealing with the pandemic are diverse. The use of digital marketing using social media platforms can increase brand awareness of MSME products. The use of digital marketing as a means of marketing communication has also been proven to increase the intensity of purchases, which has an impact on increasing income. The use of social media and the Marketplace as a means of selling has proven to be used as a medium to increase sales and, at the same time, a strategy to survive during the pandemic.